St. Lucia : Technical Assistance Report-External Sector Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
A remote technical assistance (TA) mission on external sector statistics (ESS) was conducted for the Central Statistical Office (CSO) of Saint Lucia during March 22-26, 2021. The mission was part of the Caribbean Regional Technical Assistance Centre (CARTAC) work program on External Sector Statistics (ESS).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy